Panfolliculoma with an endophytic architecture resembling a hair follicle: a report of three cases. (9th September 2016) - Terushkin, Vitaly; Meehan, Shane; Shahabi, Ladan; Brinster, Nooshin
Abstract : Panfolliculoma is a benign follicular tumor comprised of all components of the hair follicle. We report three cases of panfolliculoma with a solid, endophytic architecture, which at scanning magnification had the profile of a hair follicle. The epithelial components included uniform dark blue germinative cells, matrical cells, clear cells and cells containing trichohyaline granules. All the cases also had a central hyperkeratotic horn resembling a hair shaft. Two patients were female and one was male. Two lesions were located on the head and neck, and one was located on the leg. Clinical differential diagnoses included basal cell carcinoma, foreign body and cyst.